Patients Characteristics and Psychosocial Treatment in Psychodynamic and Cognitive Behavior Therapy - Muschalla, Beate; Linden, Michael; Rose, Matthias (Frontiers in Psychiatry, 2021)
Introduction: The most prevalent psychotherapy schools are psychodynamic (PDT) and cognitive behavior therapy (CBT). There are no scientific guidelines on which type of patient should be treated by which therapist, and how they can find the best one. Part of the answer can be derived from data on who is treated in which way. Objective: Objective of this study was to compare patients in routine PDT and CBT to describe similarities and differences in regard to patient status and treatment. Materials and Method: Research psychotherapists visited 73 cognitive behavior therapists and 58 psychodynamic psychotherapists in their office and asked them to report about the last cases they had seen. There were 188 CBT and 134 PD case reports. Results: There were no significant differences in socio-demographics between PDT and CBT patients. The average number of treatment session so far was significantly higher in PDT than CBT. There were longer duration of illness, more parallel medical treatments and higher rates of sick leave in CBT patients. While assessment of capacities with the Mini-ICF-APP showed no differences, more participation restrictions were found in CBT patients. Correspondingly there were more sociomedical interventions, especially in regard to work. Conclusions: The differences between PDT and CBT may be explained by the fact that PDT requires analytical capabilities on the side of the patient, which may exclude patients with social problems, while CBT is coping oriented which allows the inclusion of all kinds of patients. Still, in both treatment modes, complex patients are treated with multidimensional interventions.